Analisis Perubahan Struktur Organisasi dan Penerapan Upah Lembur terhadap Kinerja Karyawan (Studi Kasus pada Kantor Dinas DPMPTSP provinsi Sumatera Utara) - Ahmad Muharmansyah; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
An agency that serves investors or which oversees all companies that want to build a business in an area. The purpose of this study is to find out how employees respond and company performance when there are company policies and implementations related to changes in organizational structure that are carried out every month, as well as giving salaries when employees work overtime, while the method used is qualitative including interviews, opinions and opinions from the employee.